Development of a Digital Module for Classification of Materials and Its Changes Topic to Improve the Multi-Representation Ability of Junior High School Students - Hanifa, Deska Aisyia; Cahyono, Edy; Haryani, Sri (Universitas Negeri Semarang, 2023)
Multi-representation ability is one of the abilities that must be possessed by students, especially in science subjects to be able to understand the topics, at the chemistry level, multirepresentation abilities are divided into three, they are macroscopic, submicroscopic, and symbolic abilities. This study aims to develop a digital module for the classification of the change topics to improve the multi-representation ability of junior high school students. This research method follows development research (R&D) with the ADDIE model (analysis, define, design, develop, evaluation) with a sample of 100 class VII students at SMP Negeri 1 Kedungjati and SMP Negeri 2 Kedungjati in April 2022. The method of data collection by observation, interviews, and documentation, for data collection instruments with a questionnaire sheet. Data analysis techniques include questionnaire validity test, question validity test, questionnaire reliability test, question reliability test, digital module feasibility test, digital module practicality test and digital module effectiveness test. The conclusion of this study was that a digital module of material classification and its changes were developed based on multi-representation for class VII students whose feasibility, practicality and application could increase the classical completeness of the test, the average test scores obtained by students, and increase the multi-representation ability of students.